Tranexamic Acid Treatment of Life-Threatening Hematuria in Polycystic Kidney Disease - Turki AlAmeel; Michael West (International Journal of Nephrology)
A 41-year-old woman with autosomal dominant polycystic kidney disease had chronic kidney disease class IV. She presented 10 days postpartum with a 4-day history of severe hematuria, left flank pain, and anemia, hemoglobin 62 g/L. CT scan showed massively enlarged kidneys with multiple cysts; several cysts bilaterally had high attenuation consistent with hemorrhage. Hematuria persisted over several days despite intensive conservative measures that included vitamin K1, 4 units of plasma, transfusion of 10 units of packed RBCs, Darbopoeitin, and DDAVP. Antifibrinolytic therapy was given with tranexamic acid 1000 mg p.o. t.i.d for one day then OD. The hematuria stopped within 24 hours and did not recur after tranexamic acid therapy ended. Over the next 4 years there were 3 hospitalizations each with severe gross hematuria requiring blood transfusion for acute anemia. The hematuria responded well to further treatment with tranexamic acid. Tranexamic acid produces antifibrinolytic effects via complex interactions with plasminogen, displacing plasminogen from the fibrin surface. Chronic renal impairment is considered a relative contraindication to use of tranexamic acid due to reports of ureteric clots and acute renal failure from cortical necrosis. We conclude that tranexamic acid can be used safely in some patients with CKD and polycystic kidney disease to treat severe hematuria.